1995
DOI: 10.1021/jm00012a013
|View full text |Cite
|
Sign up to set email alerts
|

Immunospecific Reduction of Antioligonucleotide Antibody-Forming Cells with a Tetrakis-oligonucleotide Conjugate (LJP 394), a Therapeutic Candidate for the Treatment of Lupus Nephritis

Abstract: A discrete tetravalent conjugate, 7a (LJP 394), consisting of four oligonucleotides attached to a common carrier or platform was prepared. Single-stranded oligonucleotide 20-mers consisting of alternating deoxycytidine-deoxyadenosine nucleotides, (CA)10, were attached to a tetrabromoacetylated platform by displacement with sulfhydryl-terminated linkers. The tetrabromoacetylated platform 3a was synthesized in three steps using triethylene glycol bis-(chloroformate). The single-stranded conjugate was characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 4 publications
(9 reference statements)
0
37
0
1
Order By: Relevance
“…Because the binding of anti-DNA Abs to either DNA or ligands that mimic DNA is common to all three pathways, disruption of these interactions has been proposed as a novel drug design strategy. 3,8,[12][13][14][15] Thus, structural and thermodynamic analysis of Ab-DNA recognition is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Because the binding of anti-DNA Abs to either DNA or ligands that mimic DNA is common to all three pathways, disruption of these interactions has been proposed as a novel drug design strategy. 3,8,[12][13][14][15] Thus, structural and thermodynamic analysis of Ab-DNA recognition is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…3,[12][13][14] Anti-DNA Abs represent a challenging ligand design target, however, due to their inherent cross-reactivity. Several studies have reported the binding of non-DNA ligands to 0022-2836/$ -see front matter q 2005 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanism of action is to induce tolerance by cross-linking anti-dsDNA surface antibodies on B-cells, leading to B-cell anergy or apoptosis and reduced anti-dsDNA production. 45 In a phase III trial intended to evaluate whether abetimus could decrease the risk of nephritic fl ares, 317 patients with a history of lupus nephritis and elevated anti-dsDNA antibodies were randomized to abetimus or placebo. 46 Abetimus did not prolong time to renal fl are, time to major SLE fl are, or time to initiation of standard induction therapy.…”
Section: Abetimus (Ljp-394)mentioning
confidence: 99%